Measuring Ventricular Width on Cranial Computed Tomography: Feasibility of Dose Reduction in a Custom-Made Adult Phantom - Daubner, D.; Spieth, S.; Cerhova, J.; Linn, J.; Kirchhof, K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: To estimate feasible dose reduction to reliably measure ventricular width in adults with hydrocephalus in follow-up cranial computed tomography (CCT) using a custom-made phantom.Materials and Methods: A gelatine-filled adult calvarium with embedded central fibers of two carrots representing the lateral ventricles was used as a phantom. The phantom was scanned 11 times with two CT scanners (LightSpeed Ultra, GE and Somatom Sensation, Siemens), using tube currents of 380/400, 350, 300, 250, 200, 150 and 100 mA, and tube voltages of 140, 120, 100 and 80 kV. The width of the carrots was measured at four sites in consensus decision of two principle investigators blinded to the scan parameters. Values measured at 380/400 mA and 140 kV served as a reference for the width of the ventricles. Measurements received 1 point if they did not differ more than 0.5 mm from the reference values. A maximum score of 4 could be achieved.Results: The relationship between the correct width measurement of the carrots (lateral ventricles) and the radiation dose can be described by a quadratic regression function. Pixel noise increases and accuracy of measurements decreases with a lower radiation dose. Starting from a tube current of 380/400 mA and a tube voltage of 140 kV, the dose can be reduced by 76 % for LightSpeed Ultra and by 80 % for Somatom Sensation provided that a margin of error of 37.5 % (score = 2.5) for correct width measurement of the carrots is accepted.Conclusion: Lowering the radiation dose by up to 48 % for LightSpeed Ultra and by 52 % for Somatom Sensation, compared to the standard protocol (120 kV and 400 mA) still allowed reliable measurements of ventricular widths in this model.Key Points:• There is a quadratic relationship between correct width measurements of lateral ventricles and radiation dose in CT.• Reduction of radiation dose results in increased pixel noise and increased error for correct ventricle width measurement.• Due to a considerable attenuation difference between cerebrospinal fluid and brain parenchyma, a dose reduction for the determination of ventricular size in CT seems feasible and should be performed.Citation Format:• Daubner D, Spieth S, Cerhova J et al. Measuring Ventricular Width on Cranial Computed Tomography: Feasibility of Dose Reduction in a Custom-Made Adult Phantom. Fortschr Röntgenstr 2016; 188: 73 – 81
Keywords: brain; radiation dose; CT-spiral; ventricular width; hydrocephalus; adults